Effects of the Computer Mediated Communication Interaction on Vocabulary Improvement - Siamak Mirzaei; Ashkan Farrokh Hayati (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This study examined the effect of CMC interaction on Iranian EFL learners’ vocabulary improvement. The study was carried out on the basis of a comparative design and tried to compare CMC with face to-face interactions in the Iranian EFL learners in order to see whether the learners’ lexical knowledge improved by the CMC interaction. Participants of the study were advanced learners studying in a language institute. The Oxford placement test was used to determine the Iranian EFL learners’ proficiency level and ensure a homogeneous sample. Then, the participants were randomly assigned to one control group (face-to-face interaction) and one experimental group (CMC interaction) in order to compare the effect of CMC on the learners’ vocabulary improvement. The learners took a pre-test to select 12 target lexical items, treatment activity to perform information-gap task, and two immediate and delayed post-tests for assessing the acquisition of new lexical items. Yahoo Messenger was used to provide the chat communication. The research provided evidence that there was a significant relationship between the use of CMC interaction and face-to-face interaction with regard to improvement in the learners’ vocabulary learning. The result indicated that the learners’ vocabulary learning improved more in CMC interaction in comparison to face-to-face interaction. In addition, there was a significant difference in negotiating the meaning of new lexical items through CMC interaction in comparison to face-to-face interaction. Moreover, the results indicated that in terms of signal, the CMC interaction outperformed face-to-face group.